Craniofacial Approaches to Pediatric Orbital Tumors. Issue 4 (June 2019) - Kaderbhai, Jameel; Lo, William; Rodrigues, Desiderio; White, Nicholas; Evans, Martin; Nishikawa, Hiroshi; Dover, Michael Stephen
Abstract : Abstract: Primary pediatric orbital tumors requiring surgery are uncommon and often require multidisciplinary management. Commonly used surgical approaches to the orbit include transconjunctival, transcutaneous (eyelid), transcranial, or extracranial osteotomies. This paper reviews a 10-year experience of cases that required a transcranial or extracranial surgical approach at the Birmingham Children's Hospital. A total of 9 patients were identified between the years 2008 to 2017. Pathologies included rhabdomyosarcoma, juvenile ossifying fibroma, optic nerve glioma, and retinoblastoma. Surgical approaches to the orbit included supraorbital bar osteotomy (transcranial) or lateral orbitotomy (extracranial). Surgical team members included neurosurgery, craniofacial surgery, and ophthalmology. This study aims to review the role of surgery in management as well as the specific indications for performing transcranial or extracranial osteotomies. It also highlights the excellent access achieved with the use of these osteotomies in certain cases, especially when compared with transconjunctival or transcutaneous approaches.